A "Poison in The soul dificult to share" The shame in contemporary novels for young adults - Atzenhoffer, Régine (Ondina - Ondine, 2021)
This research work deals with the relationships between the literature aimed at teenagers and shame, in narratives written by French and German contemporary authoresses. These writers relate young people’s inner voicing, the shame they feel when facing their devastated bodies and their sick parents. The point is to examine the varied topical statements linked with the literary treatment of shame and its manifold instances and the perceptions of the side effects of anorexia and Alzheimer. It also analyses the impacts which mostly affect young people such as hate and anger. Keywords: youth literature, shame, anger, anorexia, Alzheimer